The foreign policy of the state in the era of the Prophet and its impact on the international arena at the time analytical study - Star AL Bayati, Abdul Jabbar (Opción, 2019)
The study deals with the subject of the foreign policy of the state in the Prophetic era. It is one of the important topics in the historical studies, because it discusses the situations of peace and its conditions, the situations of war and its repercussions. The study aims to identify the features and characteristics of the foreign policy of the Prophet; The study methodology included the most important principles governing the image of international relations, as well as the diplomatic rules and customs followed by the Apost- le Leader, and the impact of letters and correspondence and their dimensions in the world. International Square, with the presentation of the models of these letters and political analysis